PTH-203 Clinical benefits of pump infusion pressure monitoring in patients on home parenteral nutrition. (22nd June 2015) - Small, M; Kallis, M; Tsoukalis, A; Cascailh, JC; Gabe, SM
Abstract : Introduction: The role of monitoring intravenous pump infusion pressures in the early diagnosis or treatment of catheter related problems has not been fully realised. Previous industry collaboration resulted in the development of a system to monitor infusion pressures. 1 This follow on study aimed to identify the normal range of infusion pressures in patients on home parenteral nutrition and if these could aid in the diagnosis and treatment of catheter related problems. Method: 26 patients consented to have their infusion pressures monitored. Infusion pressures were recorded on the Micrel PN+ pump and exported anonymously using GPRS technology to a secure Micrelcare™ server. Any patient receiving home parenteral nutrition (not just those using the Micrel PN+) experiencing a partial or total occlusions had infusion pressures measured pre and post intervention to restore patency to their catheter. Results: 5484 infusions were recorded from 26 patients over 410 days. The average infusion pressure was 0.28 ± 0.09 (range 0.01–0.85) bar and did not increase with infusion rate (r = 0.3). 20(77%) patients had open ended devices, 4(15%) valved devices and 2(8%) had implanted ports. There was no difference in the pressure readings between devices p = 0.91. There were 69 readings above the Upper Confidence Interval of 0.56 bar from 6 patients. 60 (87%) were from 1 patient with a valved port who reported multiple downstream occlusions. These alarms stopped after changing to a longer length Huber™ needle, but high readings were still recorded. Comparison with the readings from a non valved port revealed those from the valved port were significantly higher p < 0.0001. 1 patient with clinically confirmed thrombosis had a pressure spike of 0.67 bar 5 days before presenting with symptoms. Pressures in the preceding 6 months were within normal limits (≤0.56 bar). 6 patients (all not on regular monitoring via the Micrel PN+) had a partial or total occlusion. Mean pre intervention pressure was 0.31 ± 0.048 bar, post intervention it was 0.2 bar ±0.055, p = 0.007. Conclusion: This study describes the normal range of infusion pressures in patients on home parenteral nutrition and how these can be used in the diagnosis and treatment of catheter related problems such as occlusion or thrombosis. Sudden spikes in infusion pressure may be indicative of an upcoming complication, however the extent to which these can be used to accurately predict specific complications such as thrombosis requires further analysis. Disclosure of interest: M. Small: None Declared, M. Kallis Paid Instructor for: Micrel Medical Devices, A. Tsoukalis Employee of: Micrel Medical Devices, J. Cascailh Employee of: Micrel Medical Devices, S. Gabe: None Declared. Reference: Gabe, et al. Clin Nutr. 2013;32(Suppl 1):S15